PENGEMBANGAN MODUL BILINGUAL BERGAMBAR BERBASIS MODEL PREDICT, OBSERVE, EXPLAIN (POE) PADA MATERI PELUANG - Mayang Sari; Ferinaldi; Awatif (Pendidikan Matematika | STKIP YM Bangko, 2021)
This research aims to produce a bilingual illustrated module product based on predict, observe, explain (POE) on the probability material for class VIII Junior High School/MTs which is valid and practical. The type of research developed is research and development (Research and Development) which refers to the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The instrument used was the expert expert validation sheet to measure the validity of the module and the questionnaire sheet and student interview guidelines to measure the practicality and ease of use of the module. The results showed that the assessment of the experts was very valid with the average percentage of material experts was 4.47%, the average percentage of language experts was 4.5%, and the average percentage of media experts was 4.89%. The POE-based illustrated bilingual module on the probability material also obtained a percentage value of 83.85% of the student responses in the practical category.